2014
DOI: 10.1038/aps.2014.20
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of autophagic flux in myocardial tissues is required for cardioprotection of sevoflurane postconditioning in rats

Abstract: Aim: Sevoflurane postconditioning (SpostC) has been shown to protect the heart from ischemia-reperfusion (I/R) injury. In this study, we examined whether SpostC affected autophagic flux in myocardial tissues that contributed to its cardioprotective effects in rats following acute I/R injury. Methods: SD rats underwent 30 min of left anterior descending coronary artery ligation followed by 120 min of reperfusion. The rats were subjected to inhalation of 2.4% (v/v) sevoflurane during the first 5 min of reperfusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 43 publications
(55 reference statements)
2
27
0
Order By: Relevance
“…The dose and administration route for ADT were chosen based on our previous publication, which showed that intraperitoneally administered ADT at 50 mg/kg conferred robust protection in a well-established mouse model of cerebral ischemia [6]. In addition, it has been reported that compound c at 250 mg/kg abolishes cardioprotection conferred by AMPK activators [13] and that CQ at 10 mg/kg blocks the autophagy flux following myocardial I/R [11,14].…”
Section: Experimental Groups and Drug Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The dose and administration route for ADT were chosen based on our previous publication, which showed that intraperitoneally administered ADT at 50 mg/kg conferred robust protection in a well-established mouse model of cerebral ischemia [6]. In addition, it has been reported that compound c at 250 mg/kg abolishes cardioprotection conferred by AMPK activators [13] and that CQ at 10 mg/kg blocks the autophagy flux following myocardial I/R [11,14].…”
Section: Experimental Groups and Drug Administrationmentioning
confidence: 99%
“…ROS likely accounts for beclin-1 upregulation and LAMP-2 down-regulation induced by I/R [11,14]. We used DHE to measure ROS generation as previously described [15].…”
Section: Adt Enhanced Ampk Activation and Autophagic Flux Following Mmentioning
confidence: 99%
“…In a Langendorff model of ischemia/reperfusion, inhibition of autophagy with the cell-permeable inhibitor (TATAtg5K130R) neither increased nor reduced infarct size, suggesting that in the absence of pre-or post-conditioning, the beneficial and deleterious effects of autophagy may be balanced (34). Inhibition of autophagic flux increases hypoxia/ reoxygenation injury (109) and blocks the beneficial effects of sevoflurane postconditioning (107). Ischemia/reperfusion injury disrupts autophagosome-lysosome fusion (54), accompanied by a significant increase in Beclin-1.…”
Section: Ischemia-reperfusion: An Energy Supply Crisismentioning
confidence: 99%
“…I/R injury decreases myocardial cell viability, causes cardiac dysfunction, may have a life-threatening consequence [1]. Different conditioning strategies is proved to be effective for prevention of I/R injury in animal models [1,2].…”
Section: Introductionmentioning
confidence: 99%